GLOBAL TOURISM AND CLIMATE CHANGE; CONCERNS AND STRATEGIES - PRABHA SHASTRI RANADE (ASEAN Journal on Hospitality and Tourism, 2010)
Climate change is one of the most important global environmental challenge facing humanity. Global tourism is deeply influenced by global climate change. This paper aims to study the impacts of climate change on global tourism in general and in selected countries and island nations. The increasing incidence of natural disasters is the major manifestation of climate change. Outbreak of epidemics is also considered as a consequence of climate change. These disasters pose great danger and cause severe damage to the basic infrastructure which supports tourism related activities. How global tourism is influenced by major natural disasters will be examined. Melting glaciers and rising sea levels are posing great challenge to global tourism as they are impacting several countries and islands. This aspect will also be examined. Climate change is impacting the biodiversity, which is the basic resource for tourism. Some of the instances of impacts of climate change on biodiversity and tourism will also be provided. Several countries and island nations have drawn up strategies to cope with climate change and are also implementing them. This includes the strategies to cope with climate induced disasters and protecting the tourism related infrastructure.